Leadership Model of Pesantren The Counteract of Religious Blasphemy Movement In Indonesia - Akhmad Qomaru Zaman; Dwi Retnani Srinarwati; Suhari Suhari (At-Ta'dib, 2023)
Islamic student boarding school (pesantren) an institution that operates in the fields of religion, education, and society, has recently received a sharp focus on issues of religious radicalism and terrorism. Pesantren has long been an institution that has an important contribution to participate in the intellectual life of the Indonesian nation. This study aims to analyze the leadership model in student boarding schools that can counteract the growth and development of religious radicalism movements in Indonesia. This research was phenomenological qualitative research that took place in three student boarding schools in Java, Indonesia. The three student boarding schools were the Al-Hikam Student Islamic Boarding School in Malang City, the Al-Jihad Student Islamic Boarding School in Surabaya, and the Budi Mulia Student Islamic Boarding School in Sleman Yogyakarta. Sources of data used included boarding school administrators, students, and alumni, as well as documents and archives. Data were collected through in-depth interviews, observations, document searches, and Focus Group Discussions (FGD). Data analysis was carried out phenomenologically with a systematic procedure. The research findings show that the leadership models in the three student boarding schools generally have similarities even though each pesantren has its characteristics. The leadership model in the three student Islamic boarding schools includes democratic leadership, which is managed in a systematic, open, collegial, and decentralized manner with many individuals who do not fully rely on charisma and are not completely paternalistic. This democratic leadership model has proven to be effective in countering religious radicalism movements in student boarding schools in particular and in society in general.